1999
DOI: 10.1002/lt.500050417
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosing cholestatic hepatitis in renal transplant recipients with hepatitis C virus infection

Abstract: Fibrosing cholestatic hepatitis (FCH) has been described as a specific manifestation of hepatitis B virus (HBV) infection in liver allograft recipients characterized by a rapid progression to liver failure. Only sporadic cases have been reported in other immunocompromised groups infected with HBV and in a few transplant recipients with hepatitis C virus (HCV) infection. We present the occurrence of FCH in 4 HCV-infected renal transplant recipients within a series of 73 renal transplant recipients with HCV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 24 publications
(34 reference statements)
1
40
2
Order By: Relevance
“…High viremia of this magnitude can be observed, however, when HCVinfected patients are undergoing immune suppressive therapy after transplantation. [22][23][24] Histological analysis of the liver of an HCV-infected mouse showed that most human hepatocytes were infected. Despite careful electron microscopic analysis, no viral or subviral particles could be identified in human hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…High viremia of this magnitude can be observed, however, when HCVinfected patients are undergoing immune suppressive therapy after transplantation. [22][23][24] Histological analysis of the liver of an HCV-infected mouse showed that most human hepatocytes were infected. Despite careful electron microscopic analysis, no viral or subviral particles could be identified in human hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This high level of HCV RNA indicates markedly enhanced replication of HCV, leading to direct cellular degeneration and death [13]. HCV genotype 1b was reported to have a more frequent and severe form of recurrent HCV compared with other genotypes, but these results are conflicting [4,10,18].…”
Section: Viral Factorsmentioning
confidence: 47%
“…9,10 Among our patients, only the first case was known to be HCV positive; other two patients did not show anti-HCV antibodies. Unfortunately, the search for RNA HCV was not performed on these patients before transplantation, so it is impossible to determine whether they were in a window period or whether it was an old infection.…”
Section: Discussionmentioning
confidence: 81%
“…7 Initially described in 1991 as a complication of a hepatitis B infection (HBV) in liver transplant recipient, 8 this rare entity appears to be associated with HCV infection in renal transplantation. 9 It seems to be associated with rapid viral replication in the immediate period following transplantation with the development of rapidly progressive hepatic failure with ensuing death. Herein we have presented three cases of renal transplant patients who developed FCH and underwent treatment for HCV infection.…”
Section: H Epatitis C Virus (Hcv) Infection Has a Prev-mentioning
confidence: 99%